ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA DESTINADA A LA COMERCIALIZACIÓN DE FUNDAS PLÁSTICAS BIODEGRADABLES Y DESCARTABLES PARA LOS CANTONES DE LA PARTE ALTA (PIÑAS, PORTOVELO Y ZARUMA), PROVINCIA DE EL ORO - CONDOY ACARO, MAYRA ALEJANDRA (2018)
Today there is a global trend in favor of environmental care, people increasingly consume organic products, increasingly monitor the activities of companies that threaten the environment, this event has led to the commercialization of biodegradable plastic products and Disposable to meet these needs, in order to provide a reliable and sustainable alternative to society, trade and the environment. The present research has as a general objective: "To carry out a Feasibility Study for the creation of a Company destined to the commercialization of biodegradable and disposable plastic bags for the cantons of the upper part (Piñas, Portovelo and Zaruma), Province of El Oro " based on market, technical and financial studies. For the achievement of the objectives, the methods, techniques and instruments that facilitated the obtaining and processing of the information were used. A total of 293 surveys were carried out on the merchants of the cantons of the upper part, who expressed the tastes and preferences of the products. In the results it was determined that the Market Study indicates the demand, supply and marketing plan, revealing that 100% of merchants use plastic and disposable bags (potential demand), of this amount 100% use covers plastic 6 and disposable (real demand) and 68% mociono that would be willing to acquire the product, considering this as an effective demand. As for the Technical Study, the Project Engineering, the size of the industrial plant and the location were carried out; Regarding the size, the installed capacity of 79,820 packages of plastic and disposable bags is presented, as well as the capacity used, with a market share of 15% for the first year. Regarding the Organizational Study, the company will be constituted as a limited company made up of two partners, as well as the function manuals, the Structural, Functional and Positional Organigram, with the purpose of achieving an efficient productive and administrative performance. Regarding the investment and estimated financing to execute the required project is 36,707.74 US dollars, and the way it will be financed is through the contribution of 2 partners, which will cover 59,14% of the total investment , that is to say they will contribute with 21,707,74 dollars, and the other 40.86% that is equivalent to 15,000.00 dollars, will be financed through a credit to BAN ECUADOR, with an interest rate of 11.83%. First-year marketing costs amount to US $ 133,016.61 compared to sales revenues of US $ 154,349.00, generating a net profit of US $ 12,729.04 for the first year. 7 In the Project Evaluation where the profitability of the project is measured, parameters such as: Cash flow, which for the first year is $ 19,045.17; Positive Net Present Value, which is $ 38,105.91; An Internal Rate of Return, which is higher than the capital interest rate (46,95%), Period of Capital Recovery where it is described that the investment will recover in 2 years, 6 months and 23 days; The Benefit - Cost Ratio is 0.17 cents for every dollar invested; Within the Sensitivity Analysis, an increase in costs of 5.53% is tolerated compared to a decrease of 5,20% in revenues, which makes the project feasible. Finally it was concluded that there is a large volume of unsatisfied demand of 520,041 packages of biodegradable and disposable plastic bags, for this reason it is recommended to investors and future entrepreneurs the implementation of the project in view of its great unsatisfied demand, which ensures the profitability of it.